A Comparative Evaluation of Base Isolation Effectiveness in Mitigating Seismic Response for Low-Rise and Mid-Rise Buildings - I Putu Ellsa Sarassantika; I Gusti Ngurah Agung Eka Arya Tejadinata (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Low-rise and mid-rise structures often possess natural periods that coincide with high-energy seismic response plateaus, rendering them susceptible to significant response amplification. This study evaluates the comparative effectiveness of High Damping Rubber Bearings (HDRB) in mitigating these risks for 4-story and 8-story office buildings under Indonesian seismic conditions. Using rigorous Non-Linear Time History Analysis (NLTHA) in the dominant X-direction, the research examines period elongation, lateral displacement, inter-story drift, peak floor acceleration, and base shear attenuation. Scientific findings reveal that HDRB transitions structural behavior into a near-rigid-body motion, reducing normalized inter-story drift to 0.26 and 0.12, and base shear by up to 71%. Furthermore, peak floor acceleration is curtailed by 51% to 59%, ensuring the protection of sensitive non-structural components. The results demonstrate that while base isolation provides superior seismic protection for both building scales, its efficacy in intercepting seismic energy and preventing operational disruptions is significantly more pronounced in mid-rise structures. This study confirms that HDRB is an increasingly vital strategy for enhancing functional resilience as building height increase.